Making Students Aware of the Universal Human Values - Nadiia KICHUK; Antonina KICHUK (ACROSS)
This increases the importance of higher education as a factor of socialization of students, as well as the role of the university educational process in the personal and professional development and especially that of the future teacher of the younger generation, a carrier of the values of multiculturalism.